2023
DOI: 10.3390/medicina59091661
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Microbiota in Sjögren’s Syndrome

Diana Mieliauskaitė,
Vilius Kontenis

Abstract: Primary Sjögren’s syndrome (pSS) is a heterogeneous chronic autoimmune disorder with multiple clinical manifestations that can develop into non-Hodgkin’s lymphoma in mucosa-associated lymphoid tissue. The pathogenesis of Sjögren’s syndrome (SS) is not completely understood, but it is assumed that pathogenesis of SS is multifactorial. The microbiota plays a notable role in the development of autoimmune disorders, including Sjögren’s syndrome. Molecular mimicry, metabolite changes and epithelial tolerance breakd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Autoimmune epithelitis and dryness of mucosal surface, as well as autoimmune processes, may sensitise to certain bacterial infections (78). Three pathways might help to clarify the potential contribution of microbiota to pSS pathogenesis: molecular mimicry, metabolite changes and epithelial tolerance breakdown (79). Similar type of research was made also in patients with systemic lupus erythematosus: researchers found out that several pathobionts and pathways are related to local or systemic inflammation processes and immune system dysregulation in animal lupus models, but remains to be determined how consistent they are among different patient populations and which microbial antigens drive immune intolerance to produce several lupus-related autoantibodies (80) In aggregate, some dietary approaches may improve RA symptoms and thus it is recommended that nutrition should be routinely addressed (81).…”
Section: Diet and Microbiomementioning
confidence: 99%
“…Autoimmune epithelitis and dryness of mucosal surface, as well as autoimmune processes, may sensitise to certain bacterial infections (78). Three pathways might help to clarify the potential contribution of microbiota to pSS pathogenesis: molecular mimicry, metabolite changes and epithelial tolerance breakdown (79). Similar type of research was made also in patients with systemic lupus erythematosus: researchers found out that several pathobionts and pathways are related to local or systemic inflammation processes and immune system dysregulation in animal lupus models, but remains to be determined how consistent they are among different patient populations and which microbial antigens drive immune intolerance to produce several lupus-related autoantibodies (80) In aggregate, some dietary approaches may improve RA symptoms and thus it is recommended that nutrition should be routinely addressed (81).…”
Section: Diet and Microbiomementioning
confidence: 99%